2001
DOI: 10.1016/s0925-4773(01)00512-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic temporal and spatial regulation of the cdk inhibitor p57kip2 during embryo morphogenesis

Abstract: The complete developmental expression pattern of the cyclin dependent kinase inhibitor (CDKI) p57(kip2) has not been reported, here we report a detailed study of the localization of p57(kip2) protein during mouse organogenesis. We show that p57(kip2) is coincident with key stages of differentiation of several organs, some but not all of which are affected in Beckwith-Weidermann syndrome, a human congenital syndrome characterized by foetal overgrowth and childhood tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 18 publications
6
47
1
Order By: Relevance
“…Our findings in the rat lung are consistent with the published data in the mouse 40 and hamster, 46 in that p57…”
Section: Rat P57supporting
confidence: 93%
See 2 more Smart Citations
“…Our findings in the rat lung are consistent with the published data in the mouse 40 and hamster, 46 in that p57…”
Section: Rat P57supporting
confidence: 93%
“…This difference may be due to different methodologies used. In mouse, Kochilas et al 39 found an expression pattern that was similar to that reported here, whereas others 37,40 described expression restricted to the endocardial cells of mouse at comparative embryonic stages. This discrepancy can be attributed to observational differences.…”
Section: Rat P57supporting
confidence: 85%
See 1 more Smart Citation
“…Kip2 was not only expressed by terminally differentiated cells, but was present in cells undergoing shape-changing, mitosis, and cell division (Westbury et al, 2001). …”
Section: P57mentioning
confidence: 99%
“…Immunostaining can be used to identify proliferating cells, using an antibody to Ki67 (1/1,000 dilution), to establish identity, using an antibody to Myf-5 (1/1,000 dilution), or to investigate gene expression (see Section 4.5). Immunostaining can be achieved using a number of methods, the following (described in (28,29)) is used routinely by the authors:…”
Section: Immunohistochemistrymentioning
confidence: 99%